Bullying and violence in schools: An international perspective and findings in Greece - K. Smith, Peter; Nika, Varvara; Papasideri, Margarita (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF